Transdiagnostic risk factors of emotional disorders in adults: A systematic review - Antuña-Camblor, Celia; Peris-Baquero, Óscar; Juarros-Basterretxea, Joel; Cano-Vindel, Antonio; Rodríguez-Díaz, F. Javier (Anales de Psicología / Annals of Psychology, 2024)
Comorbidity is more the rule than the exception in mental health, specifically in the case of anxiety and depression. Transdiagnostic models studied the underlying processes to improve mental health treatment and understating. Objective: This systematic review searchs for evidence on transdiagnostic risk factors for anxiety and depression in the clinical population diagnosed with these psychopathological conditions, by analysing the different types or categories of factors identified. Methods: A systematic review was registered in PROSPERO (registration number CRD42022370327) and was designed according to PRISMA-P guidelines. Two independent reviewers with field knowledge assessed the study quality to reduce bias. Results: Fifty-three articles were examined, and the transdiagnostic variables were grouped into three categories: psychological, biological, and sociocultural. Conclusions: The most studied category was that of psychological variables, especially cognitive processes, negative affect, and neuroticism, intolerance of uncertainty, anxiety sensitivity. Biological and sociocultural factors require more study to support their transdiagnostic approach.